2021
DOI: 10.1002/art.41535
|View full text |Cite
|
Sign up to set email alerts
|

Allele‐Specific Quantification of HLA–DRB1 Transcripts Reveals Imbalanced Allelic Expression That Modifies the Amino Acid Effects in HLA–DRβ1

Abstract: Objective. HLA association fine-mapping studies have shown the effects of missense variants in HLA-DRB1 on rheumatoid arthritis (RA) susceptibility, prognosis, and autoantibody production. However, the phenotypic effects of expression changes in HLA-DRB1 remain poorly understood. Therefore, we investigated the allele-specific expression of HLA-DRB1 and its effect on an HLA-DRβ1 structure-associated trait in RA. Methods. We quantified the allele-specific expression of each HLA-DRB1 3-field classic allele in 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The basic pathological changes of RA are chronic inflammation of synovium, pannus formation, and gradual destruction of articular cartilage and bone, resulting in joint deformity and loss of function [ 4 ]. At present, it is considered that HLA-DRB1 allele mutation is related to the disease [ 5 ]. In addition, abnormal immune regulation is also an important factor in the occurrence and development of RA.…”
Section: Introductionmentioning
confidence: 99%
“…The basic pathological changes of RA are chronic inflammation of synovium, pannus formation, and gradual destruction of articular cartilage and bone, resulting in joint deformity and loss of function [ 4 ]. At present, it is considered that HLA-DRB1 allele mutation is related to the disease [ 5 ]. In addition, abnormal immune regulation is also an important factor in the occurrence and development of RA.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence suggesting that expression of genes in the major histocompatibility complex (MHC) region vary significantly between different HLA-DRB1 alleles (8)(9)(10)(11). In addition, a recent study showed allele-specific expression of HLA-DRB1 in Korean ACPA-positive RA patients (12). However, these differences have not been studied in healthy individuals with susceptibility alleles in the MHC locus and for specific cell types.…”
Section: Introductionmentioning
confidence: 99%